PENGARUH MOTIVASI PEGAWAI TERHADAP PRODUKTIVITAS KERJA DI PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) SINGGANI KOTA PALU - Fitriana, Fitriana (Katalogis, 2017)
The type of this research was quantitative, with survey approach. The samples of this research amounted to 56 respondents.The sample size determination was based on the opinion of Arikunto (2002: 107), if the subjectsare less than a hundred, it is better to take them all. Thus, in this study the entire population was sampled. Data were analyzed using simple regression. The results showed the positive relationship between employee motivation and work productivity at Singgani PHC of Palu City, but when viewed from the value of the variables correlation, it was includedto enough category. Thus, it meant thatemployee motivation has relationship towork productivity at Singgani PHC of Palu City. The coefficient of determination was 0,504. This showed that the ability of employee motivation in influencing work productivity amounted to 50.4%.Employee motivation had positive or same-direction relationship towork productivity, for the regression coefficient was positive. Each unit of increase in employee motivation would result in 50.4 units of increase in work productivity. Likewise any unit of drop in employee motivation wouldresult in50.4 units of decline in work productivity.